Experimental Investigation of Vacuum Membrane Distillation (VMD) Performance Based on Operational Parameters for Clean Water Production - Iqbal Faisal; Asif Muhammad; Jafry Ali Turab; Bibi Wajeeha (MATEC Web of Conferences, 2024)
Freshwater shortage is an ongoing concern across the world, due to increasing populations and climate change. Vacuum membrane distillation (VMD) is a viable approach for producing fresh water to meet the needs of society. In the current study, an experimental investigation has been conducted on a laboratory-scale single-stage module to explore the impact of operational parameters such as feed temperature, vacuum pressure, and feed salinity on the performance of vacuum membrane distillation (VMD), including permeate flux, gained output ratio, and specific thermal energy consumption. Results show that increasing the feed temperature and feed flow rate, and reducing the salinity, increases the permeate flux. As the feed temperature rises from 60 to 70°C, the permeate flux increases from 1.90 to 4.36 kg/m²h at a permeate pressure of 12 kPa and salinity of 30 g/L. Similarly, increasing the vacuum pressure from 12 to 18 kPa reduces the permeate flux. As a result, the specific thermal energy consumption increases from 728 to 803 kWh/m³. From experimental findings, it was observed that the rejected brine from VMD retains sufficient energy that could be utilized in another desalination system.